2008
DOI: 10.1007/s11274-008-9680-z
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of root rot fungus Macrophomina phaseolina and growth enhancement of Pinus roxburghii (Sarg.) by rhizosphere competent Bacillus subtilis BN1

Abstract: Bacterial isolates having antifungal and good plant growth-promoting attributes were isolated from chirpine (Pinus roxburghii) rhizosphere. An isolate, Bacillus subtilis BN1 exhibited strong antagonistic activity against Macrophomina phaseolina, and other phytopathogens including Fusarium oxysporum and Rhizoctonia solani. It was characterized and selected for the present studies. BN1 resulted in vacuolation, hyphal squeezing, swelling, abnormal branching and lysis of mycelia. The cell-free culture filtrate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(73 citation statements)
references
References 40 publications
9
60
0
4
Order By: Relevance
“…So from antifungal activity results, the most promising culture KPSE3 was selected for bacterization in a replicated pot trial (Table 4). Similar type of results were recorded by Singh et al, 2008 they reported isolate B. subtilis BU 1 strongly inhibited growth of M. phaseolina with maximum inhibition of 74 % at 5 DAI. They also reported inhibition of F. oxysporum and Pythium sp.…”
Section: In Vitro Interaction Of Isolatesupporting
confidence: 87%
“…So from antifungal activity results, the most promising culture KPSE3 was selected for bacterization in a replicated pot trial (Table 4). Similar type of results were recorded by Singh et al, 2008 they reported isolate B. subtilis BU 1 strongly inhibited growth of M. phaseolina with maximum inhibition of 74 % at 5 DAI. They also reported inhibition of F. oxysporum and Pythium sp.…”
Section: In Vitro Interaction Of Isolatesupporting
confidence: 87%
“…In fact, IAA production by saprotrophs and endophytes has been reported to be involved in growth promotion in various plants and, thus, could be responsible, at least in part, for the presently observed plant growth promotion [62,63]. Similar combined effects are displayed by B. subtilis BN applied to chirpine seedlings where reduction in root rot symptoms caused by M. phaseolina in along with 43.6% and 93.45% increased root and shoot dry weight, respectively, are recorded as compared to the untreated control [64]. The use of bacteria as a soil treatment is more effective in suppressing disease than their use as a seed treatment [30].…”
Section: Discussionmentioning
confidence: 54%
“…A decrease in overall root and shoot weight has also been reported by Soussi et al (1998) in chickpea. This reduction in weight of plants under salt stress may be due to the inhibition or hydrolysis of reserved synthesizing food and its translocation to growing shoot parts (Singh et al 2008). Results show an increase in fresh weight and dry weight of plants grown in the presence of NaCl.…”
Section: Effect Of Salinity On Growth Of Tomato Plantsmentioning
confidence: 94%